Letter to Richard Aspinall - New South Wales. Colonial Treasury; Aspinall, Richard, active 1839. (1839)
Letter from N.S.W. Colonial Treasury to Richard Aspinall 13.7.1839, acquainting Aspinall that a deed of grant of 640 acres at Wellington is ready for delivery.
Manuscript reference no. : NLA MS 2138.
Xerox copy.
Original in private ownership.
Keywords: New South Wales. -- Colonial Treasury -- Records and correspondence; Aspinall, Richard, -- active 1839 -- Correspondence; Land tenure -- New South Wales -- Wellington